2005
DOI: 10.1111/j.1600-0722.2005.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Impacts on Daily Performance in Norwegian adults: validity, reliability and prevalence estimates

Abstract: The Oral Impacts on Daily Performance (OIDP) instrument was translated into Norwegian and reviewed for cultural and conceptual equivalence by a group of bilingual academics. A sample of employees from the University of Bergen completed the Norwegian OIDP frequency questionnaire twice. A total of 173 and 108 subjects participated in the first and the second administration, respectively, of this questionnaire. A two-stage proportionate random sample, comprising 2,000 residents (age-range 16-79 yr), was drawn fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
64
5
21

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 31 publications
19
64
5
21
Order By: Relevance
“…They reported that the missing teeth and periodontal pockets were problems and these negatively affected patients' quality-of-life. Previous studies reported a close relationship between missing teeth and OHRQoL [23,25,26]. This study also showed that social aspects were the items most affected by missing teeth.…”
Section: Discussionsupporting
confidence: 58%
“…They reported that the missing teeth and periodontal pockets were problems and these negatively affected patients' quality-of-life. Previous studies reported a close relationship between missing teeth and OHRQoL [23,25,26]. This study also showed that social aspects were the items most affected by missing teeth.…”
Section: Discussionsupporting
confidence: 58%
“…It was also found that cultural differences in subjects with own teeth do not play a role in the perception of oral problems to their quality of life. Therefore it is recommended to use some of the existing methods (9,33,35). In the field of dentistry, the Oral Health Impact Profile (OHIP) has been developed to examine whether the oral problems of individuals affect their daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to carry out a rigorous translation and validation process before an instrument developed in one culture is used in a different cultural setting [14,21-23]. This study was the first to use the OIDP index on an Iranian population.…”
Section: Discussionmentioning
confidence: 99%
“…The OIDP has been used in different studies of adult populations in Great Britain and Greece [9,10], Thailand [11], Tanzania [12], Uganda [13], and Norway [14]. The measure has proved to be reliable and valid in cross-sectional population-based studies as well as in studies of patients with specific oral disorders, such as traumatic injuries and malocclusion [15,16].…”
Section: Introductionmentioning
confidence: 99%